Escarro induzido em crianças e adolescentes com asma de difícil controle: taxa de sucesso, segurança e tolerabilidade - Cristiane de Abreu Tonelli (2011)
Objectives: review the relevant articles on the general technique of sputum induction, its rates, safety and tolerability in children and adolescents with different levels of asthma intensity. Data source: A review of literature over recent years was performed using Lilacs, Scielo and Medline databases. Data synthesis: In this review, results of the induced sputum samples from 778 children and adolescents with asthma were analyzed. The average success rate found was 76.7±9.9 (CI 95%,76.0-77.4%), considering different cut-off points for contamination by squamous cells. Cellular viability was reported in 517 samples and a rate of 59±14.9% (CI 95%, 55.5-58.5%) was found. There was a reduction of FEV1 values greater than 20% in 2.9% (CI 95%, 1.7-4.8%) and there was raised FEV1 in all patients after the short acting ß2-agonist was administered. Side effects were reported in 18.4% (CI 95%, 15.7-22.0%) of patients, and among the most frequent were a salty taste, chest tightness, coughing and a sore throat. Only three studies reported that age and/or the asthma intensity had an influence on securing an adequate sputum sample. The majority of the studies analyzed used a high output ultrasonic nebulizer with success rate varying from 60 to 95%. Only three of them (25%) used a low output nebulizer and their success rates were between 62.5 and 100%. Conclusions: The induction sputum technique is safe and well tolerated in patients with asthma and the success rate was around 76%.